Optimization of Chitosan Production from Mangrove Crab Shell Waste Using Response Surface Methodology (RSM) - Rosalina, Dian; Wijayanti, Willy (Jurnal Teknologi Pengolahan Pertanian, 2025)
This study optimized chitin extraction into chitosan from mangrove crab shells using the Response Surface Methodology (RSM) approach. Three independent factors were used: NaOH concentration (A), deacetylation temperature (B), and deacetylation time (C) at five levels (-α, -1, 0, +1, α). The NaOH concentration ranged from 43.2% to 78.8%, the deacetylation temperature ranged from 83.2°C to 116.8°C, and the deacetylation time ranged from 0.4 hours to 3.6 hours. The dependent variables were yield (Y1), degree of deacetylation (Y2), intrinsic viscosity (Y3), and molecular weight (Y4). The results of chitin deacetylation to chitosan optimization using the Design Expert program with the RSM approach led to 42 optimization formulas. The formula with the highest desirability value of 0.927 was the extraction condition using a 50% NaOH concentration, 110°C deacetylation temperature, and 1 hour deacetylation time. Chitosan obtained under these extraction conditions yielded 33.61%, a deacetylation degree of 79.2%, an intrinsic viscosity of 34.96 ml/g, and a molecular weight of 9.25 kDa. The deacetylation of the chitosan produced met the quality standards from Protan Laboratory, as deacetylation was ≥70%.